(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This research explores the use of multimedia technologies in English language teaching (ELT) and their impact on learners’ engagement, motivation, and overall language acquisition. In the digital age, traditional methods of teaching are no longer sufficient to meet the needs of diverse learners. Multimedia tools such as videos, audio recordings, interactive apps, animations, and virtual classrooms offer new ways of delivering content more effectively. The integration of visual, auditory, and interactive elements enhances students’ understanding, retention, and participation in language lessons. This study analyzes both theoretical frameworks and practical applications of multimedia in the classroom, focusing on various age groups and language levels. The methodology includes a combination of literature review, classroom observation, and experimental implementation in selected secondary school classes. Results show that students exposed to multimedia-supported instruction displayed significant improvement in vocabulary development, listening comprehension, and speaking fluency compared to those taught through traditional methods. The use of digital platforms like Kahoot, Quizlet, Duolingo, and BBC Learning English fostered collaborative learning and increased motivation. Moreover, the incorporation of videos and songs helped contextualize vocabulary and grammar, making abstract concepts more tangible. Teachers reported higher classroom engagement and more dynamic lesson delivery when multimedia was used appropriately. However, the study also highlights challenges such as unequal access to technology, overreliance on digital content, and the need for teacher training in tech-based pedagogy. Effective use of multimedia requires a careful balance between content and delivery, and teachers must be equipped with the skills to select and implement suitable resources. The research concludes that while multimedia technologies are not a replacement for solid pedagogical strategies, they serve as powerful tools to enrich and support English language instruction when used thoughtfully. These findings suggest that integrating multimedia technologies into English language teaching can enhance student outcomes and support a learner-centered approach. Future research should focus on long-term impacts, cross-cultural implementation, and the development of more accessible and inclusive multimedia resources for language learners worldwide.